2021
DOI: 10.1186/s12890-021-01414-9
|View full text |Cite
|
Sign up to set email alerts
|

Zosteriform skin metastasis caused by retrograde lymphatic migration of metastatic squamous cell lung carcinoma

Abstract: Background Zosteriform skin metastasis (ZSM) is rare, and its etiology is not well understood. ZSM is possibly derived from the retrograde movement of cancer cells through the lymphatic vessels during disease development. However, it has been difficult to demonstrate it, as no specific findings have been observed. Case presentation A 68-year-old man presented to our department with neck lymphadenopathy. After detailed examinations, squamous cell lu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
10
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 8 publications
(8 reference statements)
0
10
0
1
Order By: Relevance
“…3 In addition, a study of zosteriform metastases from lung cancer demonstrated the retrograde movement of tumor cells through lymphatic vessels using radiographical and pathological analysis. 19 In our review of zosteriform metastases of urothelial carcinoma, two cases (including ours) demonstrated tumor emboli within lymphatic vessels. Our patient had metastases to regional lymph nodes including ilioinguinal, pelvic, and mesenteric nodes, which may be involved in the drainage of skin in the L1-L3 dermatome.…”
Section: Discussionmentioning
confidence: 54%
See 1 more Smart Citation
“…3 In addition, a study of zosteriform metastases from lung cancer demonstrated the retrograde movement of tumor cells through lymphatic vessels using radiographical and pathological analysis. 19 In our review of zosteriform metastases of urothelial carcinoma, two cases (including ours) demonstrated tumor emboli within lymphatic vessels. Our patient had metastases to regional lymph nodes including ilioinguinal, pelvic, and mesenteric nodes, which may be involved in the drainage of skin in the L1-L3 dermatome.…”
Section: Discussionmentioning
confidence: 54%
“…In a study of 12 cases of zosteriform metastases from malignant melanoma, all patients with available data had concomitant metastatic involvement of regional lymph nodes 3 . In addition, a study of zosteriform metastases from lung cancer demonstrated the retrograde movement of tumor cells through lymphatic vessels using radiographical and pathological analysis 19 . In our review of zosteriform metastases of urothelial carcinoma, two cases (including ours) demonstrated tumor emboli within lymphatic vessels.…”
Section: Discussionmentioning
confidence: 60%
“…doi : 10.1503/cmaj.210551-f Voir la version anglaise de l'article ici : www.cmaj.ca/lookup/doi/10.1503/cmaj.210551 étroitement au zona et est également extrêmement douloureux. Il est rare et survient probablement par propagation lymphangitique rétrograde des cellules tumorales; le pronostic est extrêmement sombre [3][4][5][6] . Le diagnostic repose sur un fort degré de suspicion chez les patients qui ont des antécédents de cancer de la peau ou d'autres cancers et qui manifestent un érythème de type zostérien réfractaire aux antiviraux 4,5 .…”
Section: Carcinome éPidermoïde Cutané Métastatique Zostériformeunclassified
“…It is uncommon, and likely occurs through retrograde lymphangitic spread of tumour cells; it carries a dismal prognosis. [3][4][5][6] The diagnosis requires a high index of suspicion in patients with a history of skin cancer, or other cancers, who present with a zoster-like rash refractory to antiviral therapy. 4,5…”
mentioning
confidence: 99%
“…[3][4][5][6] The diagnosis requires a high index of suspicion in patients with a history of skin cancer, or other cancers, who present with a zoster-like rash refractory to antiviral therapy. 4,5…”
mentioning
confidence: 99%